2008
DOI: 10.1542/peds.2008-0118
|View full text |Cite
|
Sign up to set email alerts
|

Linking Mother and Child Access to Dental Care

Abstract: Objectives Among young children in low-income families covered by Medicaid, we estimate by racial/ethnic group whether children who have mothers with a regular source of dental care (RSDC) at baseline have greater dental utilization in the following year than children with mothers without a regular source. Patients and Methods From a population of 108,151 children enrolled in Medicaid aged 3 to 6 and their low-income mothers in Washington state, a disproportionate stratified random sample of 11,305 children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
35
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 47 publications
7
35
1
Order By: Relevance
“…McGrath et al findings were contrary to the present study as they reported that mothers with more than two children were 40% less likely to be regular attendees of oral health services compared to mothers with one or two children [24]. A different study by Grembowski et al also reported contrary to the present study by stating that mothers with greater a number of children (three or more) were also categorized as irregular attenders of oral health services compared to those who had only one or two children [25].…”
Section: Household Childrencontrasting
confidence: 99%
“…McGrath et al findings were contrary to the present study as they reported that mothers with more than two children were 40% less likely to be regular attendees of oral health services compared to mothers with one or two children [24]. A different study by Grembowski et al also reported contrary to the present study by stating that mothers with greater a number of children (three or more) were also categorized as irregular attenders of oral health services compared to those who had only one or two children [25].…”
Section: Household Childrencontrasting
confidence: 99%
“…Even in developed countries, studies indicate that dental care use in young children was better when their mothers had regular dental care [15] [16]. It was also indicated that the lower socioeconomic group especially need extra motivation and help in taking the initiative to visit the dentist [16].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Beyond these child factors, other parent (eg, education level, age, nativity) and household (eg, family structure and size, language spoken at home, area of residence) factors have been identified as important determinants of children's use of oral health services. [11][12][13][14][15] A broader, multilevel perspective could shed more light on the complex interplay of factors that influence children's (under)use of oral health services and help to inform development of new strategies that will eliminate persistent disparities. A recent approach has been to explore links between children's and parents' use and access to oral health care.…”
mentioning
confidence: 99%
“…Enabling or predisposing determinants of use of oral health services among adult caregivers could influence use of oral health services for children within the household. Grembowski et al 13 reported that in Washington state, young children of black and Hispanic mothers who were insured by Medicaid had higher dental care use when their mothers had a regular source of dental care. A cross-sectional study among low-income black children in Detroit found that parents who had preventive dental visits were 5 times as likely to take their children for dental visits when compared with parents who had never been to a dentist or had sought dental care only for treatment.…”
mentioning
confidence: 99%